Al-Watan newspaper's treatment of the Russian-Ukrainian war (Damascus University Journal of arts and humanities sciences, 2025)
The study aimed to know the extent of the Syrian Al-Watan newspaper’s interest in the subject of the Russian-Ukrainian war, to identify the main ideas and aspects that focused on them, to identify their trends and methods of persuasion, and to identify legal personalities, in addition to knowing the journalistic arts, and the various means of highlighting.This study falls within the descriptive research, Media survey method approved; The content analysis tool was used to analyze the study sample, during the time period from the beginning of June to the end of August in 2022 AD, and the sample consisted of (59) numbers, and the total press materials that were subjected to analysis were (140) articles.The study concluded that the newspaper focused on the economic and foreign political repercussions, in addition to the Russian military moves and the sanctions imposed on them, while Al-Watan newspaper focused on the idea of ​​escalation in the first place, focusing on its developments and its political and economic repercussions, while adopting neutrality in its treatment of the subject, as it dealt with the various moves associated with both sides. The war and global reactions, but it supported the Russian movesbecause the newspaper was affected by the Syrian political stances in support of the Russian military operation, in exchange for the lack of materials supporting the Ukrainian policy, and it used rational methods, followed by dualism, and Russian officials topped the list of actors and then international officials, while the percentage of press news in the newspaper increased ranked first, then commentary came in second place, and reports and conversations decreased.
Keywords: Al-Watan newspaper; Russo-Ukrainian war; newspaper treatment